Phenotypic characteristics and outcomes of late-onset urea cycle disorders - Khanh, Nguyen Ngoc; Ngoc, Can Thi Bich (Tạp chí Nghiên cứu Y học, 2025)
Urea cycle disorders (UCD) are characterized by elevated blood ammonia levels due to deficiencies in enzymes essential for urea metabolism. Early diagnosis and treatment reduce mortality and sequelae. Objective: To describe the phenotypic characteristics and treatment outcomes of late-onset UCD from 2010 to September 2021. Results: 32 patients from 27 families with a median age of onset of 30 months old (range: 2-180 months). 33.3% of patients had a relevant family history. Reasons for medical consultation included vomiting, fatigue/poor appetite, and lethargy. Clinical presentation upon admission: 68.8% had impaired consciousness, 75% exhibited vomiting and poor appetite, 15% experienced seizures, and 6.2% presented with muscle tone disorders. Laboratory findings showed hyperammonemia in 93.8% of cases, with elevated lactate, increased liver enzymes, and decreased prothrombin time in 87.5% of patients. Treatment with ammonia-lowering medications, hemodialysis, and glucose infusion successfully saved 87.5% of patients. Conclusion: Blood ammonia testing is essential in patients with altered consciousness, elevated liver enzymes, and decreased prothrombin time. Glucose infusion, ammonia-lowering medications, and hemodialysis demonstrate favorable outcomes. Urea cycle disorders (UCD) are characterized by elevated blood ammonia levels due to deficiencies in enzymes essential for urea metabolism. Early diagnosis and treatment reduce mortality and sequelae. Objective: To describe the phenotypic characteristics and treatment outcomes of late-onset UCD from 2010 to September 2021. Results: 32 patients from 27 families with a median age of onset of 30 months (range: 2-180 months). 33.3% of patients had a relevant family history. Reasons for medical consultation included vomiting, fatigue/poor appetite, and lethargy. Clinical presentation upon admission: 68.8% had impaired consciousness, 75% exhibited vomiting and poor appetite, 15% experienced seizures, and 6.2% presented with muscle tone disorders. Laboratory findings showed hyperammonemia in 93.8% of cases, with elevated lactate, increased liver enzymes, and decreased prothrombin time in 87.5% of patients. Treatment with ammonia-lowering medications, hemodialysis, and glucose infusion successfully saved 87.5% of patients. Conclusion: Blood ammonia testing is essential in patients with altered consciousness, elevated liver enzymes, and decreased prothrombin time. Glucose infusion, ammonia-lowering medications, and hemodialysis demonstrate favorable outcomes.